Políticas de morte para corpos sem lei: travestis e homens e mulheres transexuais da invisibilidade da vida ao descaso na morte - Silva, Fábio Mariano da (2019)
This thesis aims at discussing how the State have been establishing new ways of killing and dying, bespeaking a direct choice both of those who should live and those who should be vulnerable. The control of bodies and lives has become a project of which many social groups, among them LGBTT+, have been an object, although specifically transgender are in this matter the main targets. We agree that institutions such as the Law, Politics, Medicine and others have been committal in creating narratives and ways of establishing a Politics of Death — thusly undermining, under the endorsement of the State, the possibility of existence and constitution of these political subjects